Pengaruh Leverage, Profitabilitas, Size, Nilai Saham, Cash Holding, dan Bonus Plan terhadap Perataan Laba - Viktoria Angreini; Ida Nurhayati (Owner : Riset dan Jurnal Akuntansi, 2022)
Income smoothing is one way that companies do to manipulate data. Income smoothing often occurs in companies that experience losses and report profits for the next period, so that profits will look stable for the following period and the previous period, for example in a manufacturing company in the consumer goods industry sub-sector. Internal and external parties will pay attention to several factors that affect income smoothing within the company. This study aims to analyze and examine the effect of leverage, profitability, firm size, cash holding, and bonus plan on income smoothing. The population used in this study is the consumer goods industrial sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the last five years, namely 2016-2020 with a final sample of 142. The sampling method used in this study was using atechnique. Purposive sampling. The data analysis technique uses multiple regression analysis using the SPSS 26 program. The results of this study partially explain that leverage , profitability, company size, cash holding, and bonus plans affect income smoothing, while simultaneously forvariables leverage have no effect on income smoothing., the size of the company has no effect on income smoothing, and the bonus plan has no effect on income smoothing, while the profitability variable has a positive effect and cash holding has a positive effect on income smoothing.